2009
DOI: 10.1104/pp.109.147645
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bifunctional Nucleases, OmBBD and AtBBD1, Are Involved in Abscisic Acid-Mediated Callose Deposition in Arabidopsis

Abstract: Screening of the expressed sequence tag library of the wild rice species Oryza minuta revealed an unknown gene that was rapidly and strongly induced in response to attack by a rice fungal pathogen (Magnaporthe oryzae) and an insect (Nilaparvata lugens) and by wounding, abscisic acid (ABA), and methyl jasmonate treatments. Its recombinant protein was identified as a bifunctional nuclease with both RNase and DNase activities in vitro. This gene was designated OmBBD (for O. minuta bifunctional nuclease in basal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 109 publications
1
28
0
Order By: Relevance
“…Sequence analysis of the AtBBD1 protein family had previously shown that the AtBBD1 proteins contain several conserved domains, including a highly conserved region (HCR), a domain of unknown function 151 (DUF151), and a UV responsive (UVR) domain at the C-terminus [50]. However, this analysis did not identify a known DNA-binding motif; therefore, we tested whether different domains of AtBBD1 had DNA-binding activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis of the AtBBD1 protein family had previously shown that the AtBBD1 proteins contain several conserved domains, including a highly conserved region (HCR), a domain of unknown function 151 (DUF151), and a UV responsive (UVR) domain at the C-terminus [50]. However, this analysis did not identify a known DNA-binding motif; therefore, we tested whether different domains of AtBBD1 had DNA-binding activity.…”
Section: Resultsmentioning
confidence: 99%
“…Clones were sequenced from positive colonies and sequence analysis showed that multiple positive clones corresponded to AtBBD1 (Figure S1). AtBBD1 is an Arabidopsis homologue of the Oryza minuta bifunctional nuclease in basal defense response ( OmBBD1 ), which acts in abscisic-acid (ABA)-dependent callose deposition [50]. The Arabidopsis thaliana genome also contains an AtBBD1 homologue, AtBBD2, with 81% amino acid sequence identity to AtBBD1 (Figure S2C).…”
Section: Resultsmentioning
confidence: 99%
“…Callose probably promotes structureforming processes at the interface. This is in accordance with the data on callose-deficiency mutants (Dong et al 2005;Nishikawa et al 2005;You et al 2010).…”
Section: The Development Of Primexinesupporting
confidence: 92%
“…Bifunctional Nucleases (BFNs) have both RNase and DNase activities. Two BFNs in basal defense response 1 (BBD1) from Oryza minuta and Arabidopsis , OmBBD1 and AtBBD1 respectively, were investigated recently, and it was reported that these two proteins took regulatory roles in ABA-mediated callose deposition to set up an initial defense barrier against pathogenesis [74]. Interestingly, we found 2 BBD1 proteins from our microarray data, it suggests the existence of shared defensing pathways and transduction signals to abiotic and biotic stresses in plant.…”
Section: Resultsmentioning
confidence: 58%